An Unlikely Career in Satellite Ocean Biology or "OK, now what?". Issue 1 (1st May 2021) - McClain, Charles R.
Abstract: This article is a story of my career beginning in a small rural town in Missouri and culminating at NASA Goddard Space Flight Center after nearly 37 years there. Particular focus is on those who served as mentors and colleagues, studies of ocean surface waves, the "ocean color" satellite missions I was involved in, for example, the Coastal Zone Color Scanner and the Sea‐viewing Wide‐Field‐of‐View Sensor, the background of the future Plankton, Aerosol, Cloud and ocean Ecology mission, and the insights into ocean biology gained from these missions. The path was punctuated by what I call "OK, now what?" moments when the next step was unclear. At these junctures, mentors would open doors and I would need to "retool" to adapt to the science I would be involved in. Plain Language Summary: In this article, I tell the story of my career beginning in a small rural town in Missouri through over 35 years at NASA's Goddard Space Flight Center (GSFC) where I was researcher involved in the budding field of satellite remote sensing of the Earth's oceans. Along the way there were several occasions that I call "OK, now what?" moments when it was not clear what the next step would be. In every case, either an inspiration or a mentor pointed me forward. Each step required me to "retool", i.e., develop new skills. Once at GSFC, I became involved in "ocean color" satellite remote sensing, i.e., relating changes in the visible spectrum of light reflected out of the ocean to biological properties like the concentration of chlorophyll‐a, the pigment in green plants essential to photosynthesis. These satellite observations provide routine global observations of the Earth's biosphere. I was fortunate to be involved just as this technique was "getting off the ground" and experience the evolution of the technology and science behind it. Hopefully, my story will be an encouragement to young scientists who are confronted with the same uncertainties I was. Key Points: Scientific career from high school through retirement from NASA Experiences in satellite Earth remote sensing science and missions, for example, the Sea‐viewing Wide‐Field‐of‐View Sensor